Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1136/thx.46.7.508
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of community acquired pneumonia in Valencia, Spain: a multicentre prospective study.

Abstract: A year long multicentre prospective study was carried out in the Valencia region of Spain, to determine the cause of community acquired pneumonia. The study was based on 510 of 833 patients with pneumonia. Of these, 462 were admitted to hospital, where 31 patients died. A cause was established in only 281 cases-208 of bacterial, 60 of viral, and 13 of mixed infection. The most common microorganisms were Streptococcus pneumoniae (14-5%), Legionella sp (14%), Influenza virus (8%), and Mycoplasma pneumoniae (4%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
3
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 24 publications
7
55
3
8
Order By: Relevance
“…One reason for such a low rate of P. aeruginosa may have been the exclusion of nursing home patients, identifying a need for the re-evaluation of recommendations for group IVb patients when this population excludes those with HCAP. The mortality rates obtained in the present study were similar to those reported by other researchers [29,30]. However, it was found that nonadherence to ATS guidelines was associated with a more than doubling of mortality, although this was not significant on multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…One reason for such a low rate of P. aeruginosa may have been the exclusion of nursing home patients, identifying a need for the re-evaluation of recommendations for group IVb patients when this population excludes those with HCAP. The mortality rates obtained in the present study were similar to those reported by other researchers [29,30]. However, it was found that nonadherence to ATS guidelines was associated with a more than doubling of mortality, although this was not significant on multivariate analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Influenza viruses can be classified as A, B or C. Influenza A is found in humans, other mammals and birds, and is the only influenza virus known to have caused pandemics, such as the three twentieth century pandemics and the current influenza pandemic of swine origin [2]. Although the greatest proportion of mortality caused by influenza A infection is due to secondary bacterial pneumonia, the virus itself is also an important cause of community-acquired pneumonia (CAP), causing 5-10% of CAP in various case series [3,4]. As such, influenza infection is a major concern for pulmonologists and intensive care physicians.…”
mentioning
confidence: 99%
“…Recent observational studies have shown P. aeruginosa to be a rare cause of CAP and the etiologic microbe in 1% to 5% of patients with CAP (12)(13)(14)(15). On the other hand, P. aeruginosa has been reported to be the cause of severe CAP (CAP necessitating admission to the ICU or causing shock) in 1.8% to 8.3% of patients, with a case-fatality rate of 50% to 100% (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%